PERLINDUNGAN TERHADAP ANAK YANG MELAKUKAN KEJAHATAN - Antoni Antoni (An Nisa'a, 2014)
Children in principle is a picture of the future of a nation, on the shoulders of black and white they are an expectation, therefore it is appropriate that they should be protected as much as possible. Protection may include not only protection to children in general, as well as special protection should be given to children who commit crimes, because of the hope and future of a sprawling before them.ملخص: الأطفال في المبدأ هو صورة للمستقبل أمة، على أكتاف بالأبيض والأسود هم توقع، وبالتالي فإنه من المناسب أن عليهم أن تكون محمية قدر الإمكان. ويمكن أن تشمل الحماية حماية ليس فقط للأطفال بشكل عام، وكذلك ينبغي إيلاء حماية خاصة للأطفال الذين يرتكبون الجرائم، بسبب الأمل ومستقبل المترامية الاطراف من قبلهم.